ANALISIS KOORDINASI PELAKSANAAN TANGGUNG JAWAB SOSIAL DAN LINGKUNGAN PERUSAHAAN DI KABUPATEN SIAK PROVINSI RIAU - Lilis Suriani; Herman; Rido Oktaviandi (Halu Oleo University, 2024)
This research aims to analyze and explain the Coordination of Implementing Environmental and Corporate Social Responsibility in Siak Regency, Riau Province. This type of research uses a qualitative research type of descriptive method—data collection techniques using interview techniques, observation and literature studies from various sources. The results showed that the coordination of implementing the Company's social and environmental responsibility has not been maximally implemented. Based on the unity of action indicator measurement, coordination meetings between stakeholders are rarely held to unite actions. Then, the lack of information about TJSL is also a factor in the lack of communication. The inability of the TJSL forum to carry out its duties is also an obstacle, so there is a lack of supervision of companies, which results in companies not complying with regulations, such as making reports on the implementation of TJSL in Siak District.